Legal orderings of waste in built spaces. Issue 1 (13th April 2015) - Parizeau, Kate; Lepawsky, Josh
Abstract : Purpose: – This paper aims to investigate by what means and to what ends waste, its materiality and its symbolic meanings are legally regulated in built environments. Design/methodology/approach: – The authors investigate the entanglement of law and the built environment through an analysis of waste-related legal case studies in the Canadian context. They investigate a notable Supreme Court case and three examples of Canadian cities' by-laws and municipal regulations (particularly regarding informal recycling practices). They mobilize what Valverde calls the work of jurisdiction in their analysis. Findings: – The authors argue that the regulation of waste and wasting behaviours is meant to discipline relationships between citizens and governments in the built environment (e.g. mitigating nuisance, facilitating service provision and public health, making individuals more visible and legible in the eyes of the law and controlling and capturing material flows). They find that jurisdiction is used as a flexible and malleable legal medium in the interactions between law and the built environment. Thus, the material treatment of waste may invoke notions of constraint, freedom, citizenship, governance and cognate concepts and practices as they are performed in and through built environments. Waste storage containers appear to operate as black holes in that they evacuate property rights from the spaces that waste regularly occupies. Originality/value: – There is scant scholarly attention paid to legal orderings of waste in built environments. This analysis reveals the particular ways that legal interventions serve to construct notions of the public good and the public sphere through orderings of waste (an inherently indeterminate object).